2020
DOI: 10.1111/medu.14063
|View full text |Cite
|
Sign up to set email alerts
|

Motivational factors influencing student intentions to practise in underserved areas

Abstract: Context Exploring student intentions to practise in underserved areas (UAs) is necessary to inform the planning and training of the future medical workforce in order to increase effectiveness and fulfil societal needs. However, little is known about the motivational factors influencing these intentions. This paper explores medical students’ intentions to practise in UAs and the motivational factors predicting these intentions. Methods Eligible participants included graduating medical students from four of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…In both analyses, we found a similar aggregation of motivational factors. 1,3 This supports our epistemological assumption that medical career choice is part of a addressing negative medical student perceptions during these experiences may increase practise in underserved areas. 5 As in other European countries, Swiss students tend to study in their region of origin as a result of cultural and language differences despite the fact that physical proximity to urban areas is not a hindrance.…”
supporting
confidence: 70%
“…In both analyses, we found a similar aggregation of motivational factors. 1,3 This supports our epistemological assumption that medical career choice is part of a addressing negative medical student perceptions during these experiences may increase practise in underserved areas. 5 As in other European countries, Swiss students tend to study in their region of origin as a result of cultural and language differences despite the fact that physical proximity to urban areas is not a hindrance.…”
supporting
confidence: 70%
“…Identification with another discipline [ 12 ]; personal connections to another region [ 7 , 15 , 16 ]; unwilling to work in the countryside [ 31 ]; parents/partner are/is settled in another region [ 7 , 15 ]; financial support is insufficient [ 15 , 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Identification with another discipline [12]; personal connections to another region [7,15,16]; unwilling to work in the countryside [31]; parents/partner are/is settled in another region [7,15]; financial support is insufficient [15,31]. This list is supplemented by reasons given by students in communication with the project staff: "not willing to commit long-term" and "planned to take over the practice from parents/acquaintances in another region".…”
Section: What Are the Reasons For Not Participating In Thementioning
confidence: 99%
See 1 more Smart Citation
“…In our previous research, we explored the areas of intention to practice (urban and rural) of graduating students at 4 Swiss medical schools [ 30 ]. We found that 13.7% expressed an intention to practice in underserved areas (62.1% of whom intended to practice in rural areas) and 41.1% were undecided.…”
Section: Introductionmentioning
confidence: 99%